Putting performance and kinematics differ with skill level in female golfers - Wu, Y.-L.; Huang, C.-F.; Marquardt, C.; Wang, H. T. (The Open Sports Sciences Journal, 2020)
Background: Female professional golf tours are gaining popularity around the world; there are key performance factors that are related to high performance on the female professional tour, like "driving distance and accuracy" and "putting per round". However, there is a lack of research on the putting kinematics of female golfers with a lack of understanding the differences between the skill levels of female golfers.